The Practice of Inclusive Education of Children with Disabilities: The Quality of Competence Support - Vitaly Z. Kantor; Yuliya L. Proekt; Irina E. Kondrakova; Olga V. Litovchenko; Svetlana E. Zalautdinova (Интеграция образования, 2023)
Introduction. The aim of this paper was to look into the status of competence-based support for the inclusive education of children with disabilities from the standpoint of the unity of the competence-based approach to the preparation and professional activity of a teacher at an inclusive educational organization. Its relevance is defined by the need to determine the level of formation of inclusive competence of teachers in its direct correlation with the competence models embedded in the programs of inclusive-oriented university’s training of teachers. Materials and Methods. The study involved 1 340 teachers working in inclusive educational organizations of general and additional education. They do not have university training in the field of defectology. The diagnostic and methodological basis for assessing the level of formation of inclusive professional competencies of a teacher was the authors-developed test that combined test tasks to identify the readiness of teachers to implement the right professional actions and decisions in conditions of inclusion. Results. The results obtained indicate the imbalance in the formation of the key components of the professional competencies of teachers for inclusive education. Teachers have the most pronounced inclusive competencies in the field of individual or joint support with other specialists of a child with disabilities in the educational process and the organization of an individual learning route for him/her. The least pronounced component of inclusive professional competencies is the knowledge about development of children with disabilities. The success of solving situational problems is mediated by the nature of teachersʼ activities and their inclusive practice experience. Discussion and Conclusion. The research materials may be in demand when designing training programs, professional retraining and advanced training of teachers of inclusive educational organizations, as well as in the framework of express diagnostics of the level of formation of inclusive competencies of teachers.